The impact of TFPI on coronary atherosclerotic burden - Kahraman, S.; Erdim, R.; Helvacioglu, F.; Dogan, A.; Sozer, V; Gunay, D.; Aytekin, S.; Aytekin, V (COMENIUS UNIV, 2018)
OBJECTIVES: We aimed to associate a coronary artery disease (CAD) presence and severity with endothelial dysfunction (ED), carotid intima media thickness (CIMT) and Tissue Factor Pathway Inhibitor (TFPI). BACKGROUND: ED has a central role in atherosclerosis. CIMT and TFPI activity are also related with atherosclerosis and CAD. METHODS: In our prospective observational study, 50 patients had CAD and 30 had normal coronary arteries. Endothelial function was evaluated by endothelium-dependent flow-mediated dilatation (FMD) and nitroglycerinemediated dilatation (NMD) measurements. CIMT and Serum TFPI levels were also measured. RESULTS: TFPI was a statistically significant determinant between the two groups with an increased level in CAD (+) group (84.9 +/- 19.3 vs 70.2 +/- 14.7, p = 0.001). There was a positive correlation between CIMT and Gensini (r = 0.34, p = 0.014). There was a strong negative correlation between Gensini and FMD-NMD, statistically significant (FMD: r =-0.715, p < 0.001; NMD: r = -0.718, p < 0.001). CONCLUSION: We observed that ED, increased CIMT and TFPI levels were associated with CAD. Additionally, increased CIMT measurements and decreased FMD and NMD values had a positive correlation with GSS (Tab. 4, Fig. 6, Ref. 50). Text in PDF www.elis.sk.
Keywords: coronary artery disease; endothelial dysfunction; tissue factor pathway inhibitor; FACTOR PATHWAY INHIBITOR; FLOW-MEDIATED VASODILATION; TISSUE FACTOR; HEART-DISEASE; ARTERY-DISEASE; BRACHIAL-ARTERY; PROGNOSTIC VALUE; SMOOTH-MUSCLE; RISK-FACTORS; General & Internal Medicine